Rubber Nanocomposites and Nanotextiles : Perspectives in Automobile Technologies - Banerjee, Bireswar (De Gruyter, 2019)
This book describes rubber nanocomposites and their applications in the automobile sector. Newly developed nanofibres and nanofinished textiles, with their novel characteristics and various applications in next-generation automobiles, are also discussed. Lastly, a comprehensive evaluation and overview of the impact of nanotechnology on the textiles in automobile industries are presented.- Resumé vydavatel
Keywords: kaučuk; nanokompozitní materiály; nanotextilie; nanovlákna; automobilový průmysl; rubber; nanocomposites; nano textile fabrics; nanofibers; automobile industry; elektronické knihy; sborníky; electronic books; papers of several authors